Stacking‐Fault Enhanced Oxygen Redox in Li2MnO3. Issue 18 (16th March 2022) - Li, Xiang; Li, Xinhao; Monluc, Lisa; Chen, Benjamin; Tang, Mingxue; Chien, Po‐Hsiu; Feng, Xuyong; Hung, Ivan; Gan, Zhehong; Urban, Alexander; Hu, Yan‐Yan
Abstract: Lattice oxygen redox yields anomalous capacity and can significantly increase the energy density of layered Li‐rich transition metal oxide cathodes, garnering tremendous interest. However, the mechanism behind O redox in these cathode materials is still under debate, in part due to the challenges in directly observing O and following associated changes upon electrochemical cycling. Here, with 17 O NMR as a direct probe of O activities, it is demonstrated that stacking faults enhance O redox participation compared with Li2 MnO3 domains without stacking faults. This work is concluded by combining both ex situ and in situ 17 O NMR to investigate the evolution of O at 4i, 8j sites from monoclinic C2/m and 6c(1), 6c(2), 6c(3) sites from the stacking faults (P31 12). These measurements are further corroborated and explained by first‐principles calculations finding a stabilization effect of stacking faults in delithiated Li2 MnO3 . In situ 17 O NMR tracks O activities with temporal resolution and provides a quantitative determination of reversible O redox versus irreversible processes that form short covalent OO bonds. This work provides valuable insights into the O redox reactions in Li‐excess layered cathodes, which may inspire new material design for cathodes with high specific capacity. Abstract : Stacking faults stabilize delithiated‐Li2 MnO3 and promote reversible oxygen redox ≤ 4.5 V. Electrons delocalize within the π(Mn–O) complex of delithiated‐Li2 MnO3 . Various oxygen species in ideal and stacking‐fault Li2 MnO3 are distinguished and monitored with both in situ and ex situ 17 O NMR, revealing enhanced oxygen redox activities at stacking faults.